Joint ventures in construction - Kobayashi, Kiyoshi (Thomas Telford Limited, 2009)
Contractual relationships in international joint venture projects can be affected by different cultural foundations, language barriers, political sensitivities, and the uncertainties and risks involved throughout the life of a construction project.